Biological response of an in vitro human 3D lung cell model exposed to brake wear debris varies based on brake pad formulation - Barosova, Hana; Chortarea, Savvina; Peikertova, Pavlina; Clift, Martin J D; Petri-Fink, Alke; Kukutschova, Jana; Rothen-Rutishauser, Barbara (Archives of toxicology, 2018)
Wear particles from automotive friction brake pads of various sizes, morphology, and chemical composition are significant contributors towards particulate matter. Knowledge concerning the potential adverse effects following inhalation exposure to brake wear debris is limited. Our aim was, therefore, to generate brake wear particles released from commercial low-metallic and non-asbestos organic automotive brake pads used in mid-size passenger cars by a full-scale brake dynamometer with an environmental chamber simulating urban driving and to deduce their potential hazard in vitro. The collected fractions were analysed using scanning electron microscopy via energy-dispersive X-ray spectroscopy (SEM-EDS) and Raman microspectroscopy. The biological impact of the samples was investigated using a human 3D multicellular model consisting of human epithelial cells (A549) and human primary immune cells (macrophages and dendritic cells) mimicking the human epithelial tissue barrier. The viability, morphology, oxidative stress, and (pro-)inflammatory response of the cells were assessed following 24 h exposure to ~ 12, ~ 24, and ~ 48 µg/cm2 of non-airborne samples and to ~ 3.7 µg/cm2 of different brake wear size fractions (2-4, 1-2, and 0.25-1 µm) applying a pseudo-air-liquid interface approach. Brake wear debris with low-metallic formula does not induce any adverse biological effects to the in vitro lung multicellular model. Brake wear particles from non-asbestos organic formulated pads, however, induced increased (pro-)inflammatory mediator release from the same in vitro system. The latter finding can be attributed to the different particle compositions, specifically the presence of anatase.
Keywords: kokultivační techniky; biologické modely; velikost částic; Cytokines; Lung; oxidační stres; makrofágy; Dendritic Cells; Particle Size; dendritické buňky; povrchové vlastnosti; Oxidative Stress; cytokiny; motorová vozidla; lidé; Models, Biological; Macrophages; A549 Cells; Particulate Matter; Motor Vehicles; Humans; Air Pollutants; Coculture Techniques; plíce; Cell Survival; viabilita buněk; látky znečišťující vzduch; Surface Properties; buňky A549; pevné částice